Student Assistance as an Effort to Improve Understanding of Local History in The City of Banjarmasin - Mutiani, Mutiani; Safitri, Desy; Rusmaniah, Rusmaniah; Syarifuddin, Syarifuddin; Jumriani, Jumriani; Fazri, Ahmad (Journal of Social Development, 2024)
Local community involvement can also be an effective strategy in assisting students in junior high school. Involving community leaders, historians and local cultural figures can provide valuable perspectives and direct experience of local history to students. This service aims to determine efforts to assist students in increasing understanding of local history in the City of Banjarmasin. The method used is a mentoring activity involving Social Sciences Education students, FKIP, Lambung Mangkurat University and students at SMP Negeri 1 Tamban. The Wasaka Banjarmasin Museum also encourages students' curiosity and enthusiasm for learning. The interactive and fun learning experience at this museum motivates them to dig deeper into the local history of Banjarmasin and seek information from various sources. This will foster their love of science and encourage them to continue learning and developing. More than just an educational tourist spot, the Wasaka Banjarmasin Museum is a forum for building a sense of solidarity and unity among students.